Under-Recognized Macrophage Activation Syndrome in Refractory Kawasaki Disease: A Wolf in Sheep's Clothing - Sangwon Rhee; Danbi Kim; Kyoungsoon Cho; Jung Woo Rhim; Soo-Young Lee; Dae Chul Jeong (MDPI AG, 2022)
Recognition of macrophage activation syndrome (MAS) in patients with refractory Kawasaki disease (KD) can be challenging. This study aimed to investigate the incidence of MAS in patients with refractory KD and to compare the characteristics of refractory KD and MAS. Medical records of 468 patients diagnosed with KD from January 2010 to December 2019 were retrospectively reviewed. Of the 468 KD patients, 63 were enrolled in the study as a refractory KD group (n = 59) and an MAS group (n = 4). The incidence of MAS was 0.8% (4/468) in patients with KD and 6.3% (4/63) in patients with refractory KD. Compared to the refractory KD group, the MAS group had higher frequencies of incomplete KD, hepatosplenomegaly, third-line treatment, and MAS screening, and showed lower levels of albumin. No significant differences were found in other clinical and laboratory findings. In addition to four patients with MAS, five patients with refractory KD who received third-line treatment showed severe systemic inflammation and organ dysfunction, but only one in five patients underwent MAS screening, including ferritin levels. In conclusion, given the relatively high incidence of MAS in children with refractory KD and the similar phenotype between refractory KD and MAS, we propose that MAS screening should be included in routine laboratory tests for refractory KD.